2022
DOI: 10.1080/02713683.2021.2002910
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Two Inducible Cre Recombinase-Based Mouse Models NG2-CreER™ and PDGFRb-P2A-CreERT2 for Pericyte Labeling in the Retina

Abstract: Supplementary Figure 1: Separated visualization of tdTomato and NG2 labeling in the superficial capillary layer in retinal whole mounts at the three TAM induction time points: NG2 labeling of PCs and vSMCs (A-C) as well as tdTomato expression of PCs (arrowheads, A'-C') in the NG2-CreER TM -tdTomato mouse model. In the PDGFRb-P2A-CreER T2 -tdTomato mouse model PCs (representative arrowheads) and vSMCs are labeled with NG2 (D-F), tdTomato expression is detected in PCs (representative arrowheads) and vSMCs and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…This showed that KO of TMEM16A reduced the ET-1 evoked constriction of capillaries by pericytes (Figure 5A-B) as was also seen when using pharmacological inhibition of TMEM16A. The smaller effect of the KO in Figure 5A, compared to pharmacological inhibition in Figure 4B, likely reflects the incomplete KO achieved with Cre (the reported percentage of cells, probably oligodendrocyte precursor cells, that undergo recombination was ~60% at 2 weeks after tamoxifen administration for the Cre line we used (49) although in retinal pericytes using a different NG2-Cre line (50) it was only ~30%).…”
Section: Resultsmentioning
confidence: 83%
“…This showed that KO of TMEM16A reduced the ET-1 evoked constriction of capillaries by pericytes (Figure 5A-B) as was also seen when using pharmacological inhibition of TMEM16A. The smaller effect of the KO in Figure 5A, compared to pharmacological inhibition in Figure 4B, likely reflects the incomplete KO achieved with Cre (the reported percentage of cells, probably oligodendrocyte precursor cells, that undergo recombination was ~60% at 2 weeks after tamoxifen administration for the Cre line we used (49) although in retinal pericytes using a different NG2-Cre line (50) it was only ~30%).…”
Section: Resultsmentioning
confidence: 83%
“…Unequivocal pericyte identification remains a limitation in the field of vascular biology given the lack of a unique molecular marker (Mayr et al, 2021). Compounding this challenge are the recently described heterogeneities in pericyte morphology across microvascular networks (Grant et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Confident identification of pericytes remains an obstacle in field, as a single molecular marker for these unique perivascular cells remains elusive (Mayr et al, 2021). Adding to this challenge is the recent appreciation that PC populations may be heterogeneous, displaying a range of morphologies within capillary networks (Grant et al, 2019).…”
Section: Discussionmentioning
confidence: 99%